MENGUKUR EFEKTIVITAS DAN PEMODELAN SISTEM ANTRIAN PADA POLSEK PAMULANG KOTA TANGERANG SELATAN - Yumniati Agustina; Aminudin . (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
Bureaucracy services in Indonesia haven’t given satisfaction to the society. One of services that always complained is about queue problem. Queue system that isn’t optimal will give society’s dissatisfaction. Among bureaucracy systems that need to get concern is queue at PolsekPamulang-Kota Tangerang Selatan especially at SKCK service. So that, it is needed to be done a research to analyze and testing queue system modeling which has been applied by PolsekPamulang for SKCK service, analyze the effectiveness of the queue system performance of PolsekPamulang, and to determine the optimal number of services (counters)that should be used by PolsekPamulang. Method of research was done by queue theory approach. The research findings showed that queue of SKCK services at PolsekPamulang based on steady state calculation wasn’t effective.Because the steady state value still far from one number. The total of counter (a unit only) for SKCK service is still optimal, because of waiting time (queue) is still low. The length of queue on the system isn’t because of the large number of applicants, but it’s more focus on service standard to verify the document that needs more than 30 minutes for each document.